AMERICAN ACCOUNTING ASSOCIATION. - Garner, S. Paul; Hassler, Russell H.; Heilman, Ernest A.; Wixon, Rufus; Miller, Hermann C. (The Accounting Review, 1954)
The present Standards Rating Committee of American Accounting Association was appointed in 1949 for a period of five years upon the authorization of the Executive Committee of the Association Committee. The present committee was officially constituted and began functioning on January 1, 1949. Meetings of the committee have been held at intervals throughout the last five years. After extended discussion and rewriting over a period of two years this committee published an interim report in the January 1951, issue of Accounting Review. Full publicity was given to this interim report; suggestions, comments, and criticisms were solicited. Several members of the Association and other interested persons responded to the invitation. This committee appreciates the excellent suggestions made by correspondents. Their recommendations have been reviewed carefully along with the further thinking of the committee members themselves. After further weighing for about a year the problems confronting the committee, it was decided in early 1953 to prepare a final report in order to bring its current activities to a conclusion. Following this decision the committee has quite actively pursued its objectives and the present report represents the culmination of its efforts for the past five years.